Side Channel Attacks - Hong, Seokhie (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This Special Issue provides an opportunity for researchers in the area of side-channel attacks (SCAs) to highlight the most recent exciting technologies. The research papers published in this Special Issue represent recent progress in the field, including research on power analysis attacks, cache-based timing attacks, system-level countermeasures, and so on.